Epidemiological profile of caries and need for dental extraction in a Kaingang adult Indigenous population - Gustavo Hermes Soares; Amanda Silva Aragão; Antônio Carlos Frias; Renata Iani Werneck; Maria Gabriela Haye Biazevic; Edgard Michel-Crosato
ABSTRACT: Introduction: The epidemiological profile of dental caries for Indigenous Peoples is complex and heterogeneous. The oral health of the Kaingang people, third largest Indigenous population from Brazil, has not been investigated so far. Objective: The purpose of this study was to assess the prevalence and severity of dental caries, in addition to the associated factors of the need of dental extraction among Kaingang adult Indigenous. Methods: A cross-sectional oral health survey was conducted among Kaingang adults aged from 35 to 44 years old living in the Guarita Indigenous Land, Rio Grande do Sul. Clinical exams were performed to analyze the conditions of dental crown and treatment needs. Results: A total of 107 Indigenous adults were examined. Mean DMFT score was 14.45 (± 5.80). Two-thirds of the DMFT score accounted for missing teeth. Anterior lower dentition presented the highest rates of sound teeth, whereas the lower first molars had the lowest. Need for dental extraction was observed in 34.58% and was associated with village location, time of last dental visit, and higher number of decayed teeth. Conclusion: The high frequencies of caries and missing teeth observed in this population indicate a lack of adequate assistance. It is essential to discuss health care models in order to combat avoidable social and health injustices.